Peningkatan Pengetahuan Tentang Pencegahan Stunting dan Pemenuhan Gizi Anak pada Kader Nasyiatul ‘Aisyiyah - Sisca Windy Prastika; Nida Alfatwa; Puput Lisandra; Kholifatul Khikmah; Ayu Ferina; M. Arsyi Maulvi; Dwiky Pramana; Wulan Agustin Ningrum; Nuniek Nizmah Fajriyah (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Nutritional problems in Indonesia are still a serious problem. Nutritional problems in children are still ranked number one worldwide, especially in Indonesia, such as stunting. Stunting is a chronic malnutrition problem caused by insufficient nutritional intake for a long time resulting from the provision of food that is not in accordance with nutritional needs. One of the main causes is the poor economic situation and limited knowledge about nutrition. Nutritional status is a measure of success in meeting the nutritional needs of children and the use of nutrients indicated by the child's weight and height. The purpose of this community service is to increase mothers' knowledge about stunting prevention and fulfilling child nutrition. The methods used were: (1) Counseling, (2) Video showing the making of pumpkin pudding, (3) Pre Test, (4) Post Test. The results of this counseling show an increase in mothers' knowledge and understanding regarding stunting prevention and nutritional fulfillment in toddlers which is know from the pos test result of 55%..